Pulmonary actinomycosis masquerading as lung cancer: a case report - Boo, Yang Liang; How, Kang Nien; Pereira, Decena Shamini; Chin, Pek Woon; Kan, Foong Kee; Lim, Suat Yee (Malaysia Medical Association, 2017)
Pulmonary actinomycosis is a rare yet important and challenging diagnosis to make. It is commonly confused with other lung diseases, such as tuberculosis and bronchogenic carcinoma, leading to delay diagnosis or misdiagnosis. A 49-year-old man presented with a chronic cough, hemoptysis, and pleuritic chest pain. His initial imaging studies including computed tomography (CT) was suggestive of bronchogenic carcinoma. A subsequent CTguided biopsy was consistent with pulmonary actinomycosis and excluded the possibility of bronchogenic carcinoma. He was treated with antibiotic therapy and achieved remission with complete radiological resolution upon follow-up.